2009 6th International Multi-Conference on Systems, Signals and Devices 2009
DOI: 10.1109/ssd.2009.4956743
|View full text |Cite
|
Sign up to set email alerts
|

Model for the behavior of magnetic materials hysteretic taking into account the temperature

Abstract: The work is to develop a model for magnetic hysteresis taking into account the temperature. We introduced the effect of temperature through behavior as a function of temperature settings and model Jiles Atherton. The results of the model in terms of saturation induction, remanent induction, coercive field and the evolution of hysteresis cycle as a function of temperature are accort with theory and with results given in [1]. A program for calculating field incorporating model hysteresis to study a system of ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Simplified 2-D formulation to investigate transient phenomenon of a current transformer [13], magnetization characteristics and excitation current of single phase transformer in Matlab under dc bias field [14] has been presented using J-A model. Magnetic hysteresis in terms of saturation induction, remanent induction, coercive field and the evaluation of hysteresis as a function of temperature [15] and static and dynamic major B-H loops to study the behaviour of a current transformer focusing on thermal stress on magnetic materials under Curie temperature [16] have been computed by Jiles-Atherton model. From the literature it is showed that the large strain and force output of magnetostrictive material commercially known as Terfenol-D has led numerous researchers to spotlight on its uses for various applications more importantly in automotive applications such as in clutch and brakes.…”
Section: Introductionmentioning
confidence: 99%
“…Simplified 2-D formulation to investigate transient phenomenon of a current transformer [13], magnetization characteristics and excitation current of single phase transformer in Matlab under dc bias field [14] has been presented using J-A model. Magnetic hysteresis in terms of saturation induction, remanent induction, coercive field and the evaluation of hysteresis as a function of temperature [15] and static and dynamic major B-H loops to study the behaviour of a current transformer focusing on thermal stress on magnetic materials under Curie temperature [16] have been computed by Jiles-Atherton model. From the literature it is showed that the large strain and force output of magnetostrictive material commercially known as Terfenol-D has led numerous researchers to spotlight on its uses for various applications more importantly in automotive applications such as in clutch and brakes.…”
Section: Introductionmentioning
confidence: 99%